2007
DOI: 10.1089/mdr.2007.711
|View full text |Cite
|
Sign up to set email alerts
|

First Characterization in Tunisia of a TEM-15, Extended-Spectrumβ-Lactamase-ProducingKlebsiella pneumoniaeIsolate

Abstract: Klebsiella pneumoniae CH0905 strain exhibiting high-level cefotaxime resistance was isolated from a stool culture in the intensive care unit. The resistance gene responsible was shown to be located on a conjugative 60-kb plasmid designated pCH0905. The minimum inhibitory concentration (MIC) values for cefotaxime and ceftazidime of the original isolate and the transconjugates were 256 mug/ml. Isoelectric focusing of a protein preparation from the K. pneumoniae strain showed beta-lactamases with the pI values of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Among the 87 isolates, about twothirds produced ESBLs. Several studies have also shown the emerging problem of ESBL-producing E. coli and K. pneumoniae isolates in different geographic regions, including the Mediterranean basin [19] and North Africa [9,[20][21][22][23]. In our work, blaCTX-M-15 was the most frequently detected (54%) gene in the ESBLpositive Tunisian and Libyan isolates.…”
Section: Discussionsupporting
confidence: 55%
“…Among the 87 isolates, about twothirds produced ESBLs. Several studies have also shown the emerging problem of ESBL-producing E. coli and K. pneumoniae isolates in different geographic regions, including the Mediterranean basin [19] and North Africa [9,[20][21][22][23]. In our work, blaCTX-M-15 was the most frequently detected (54%) gene in the ESBLpositive Tunisian and Libyan isolates.…”
Section: Discussionsupporting
confidence: 55%
“…The prevalence of ESBL and AmpC enzymes has increased worldwide [50,51,52]. However, the dissemination of ESBL and AmpC enzymes has also been reported in the neighboring country Tunisia [21,38,53,54,55]. In Saudi Arabia, Kader and his group (2005) also isolated ESBL-producing uropathogens from both inpatients and outpatients.…”
Section: Discussionmentioning
confidence: 99%